The anthropogenic transformation of an island landscape: Evidence for agricultural development revealed by LiDAR on the island of Efate, Central Vanuatu, South‐West Pacific. Issue 1 (22nd August 2017) - BEDFORD, STUART; SIMÉONI, PATRICIA; LEBOT, VINCENT
ABSTRACT: Traditional agricultural systems have been a fundamental research focus of Pacific archaeologists for decades. In many island groups, it has been demonstrated that whole landscapes have been transformed to facilitate increased agricultural production. High‐resolution digital elevation models (DEM) derived from recent LiDAR survey data from Efate, Central Vanuatu, have now revealed that much of that island was completely modified by human activity prior to European contact. There are a range of substantial and more minor linear mound and circular features associated with agricultural development and innovation, of which researchers and contemporary populations are largely unaware. Detailed analysis of the features across one alluvial plain provides some quantification of the scale of landscape modification. These new data radically change perceptions of the Efate landscape and contribute to a range of debates including traditional Pacific Island food production, its surplus and sustainability, sociopolitical development, environmental change and depopulation.